Auditory stimulation modulates CXCL12/CXCR4 expression in postnatal development of the newborn rat cochlea. Issue 12 (19th August 2015) - Zhang, Wen; Zhang, Fangjun; Han, Yu; Liu, Hui; Wang, Ye; Yue, Bo; Chen, Jun; Chen, Yang; Gao, Ya
<x xml:space="preserve">Abstract</x> Sensorineural hearing loss is one of the most common sensory deficits. Recently, inner-ear stem cell therapy has been proposed for auditory afferent rehabilitation. CXCR4 is the primary physiologic receptor for CXC chemokine ligand 12 (CXCL12) and the CXCL12–CXCR4 pathway has been implicated in the process of migration, differentiation, and maturation of vertebrate neural stem cells. In this study, we examined changes in the auditory brainstem response and CXCL12/CXCR4 expression in newborn rat cochleae under different acoustic environments by quantitative real-time PCR, western blot, enzyme-linked immunosorbent assay, immunohistochemistry, and immunofluorescence analyses. Rats were divided randomly into three groups: the augmented acoustic environment (AAE) group, the auditory deprivation (AD) group, and the control group. Auditory brainstem response thresholds were markedly increased in the AAE group and in the AD group. Compared with postnatal day 1, the expression of CXCL12/CXCR4 mRNA and protein under normal acoustic conditions was increased on postnatal day 14 and then decreased on postnatal day 28 in the cochlea. However, on postnatal day 28, CXCL12/CXCR4 expression, as well as its spatiotemporal distribution as detected by immunohistochemistry and immunofluorescence assays, was augmented by AAE treatment and inhibited by AD treatment. Therefore, our results confirmed that auditory stimulation influenced the spatiotemporal expression of CXCL12/CXCR4 in newborn rat cochlea, which might help to unravel the role of the CXCL12–CXCR4 pathway in the synaptic contacts and hearing function establishment in rat cochlea development.